Цифровой метод измерения коэффициента направленного отражения поверхности - Ivanchenko, I. A.; Santoniy, V. I.; Smyntyna, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The connection between the reflectance of a surface and the coordinate of picture in a photodetector plane is established. The digital method of measurement of reflectance with application of the multielement photodetector is developed. This method allows increasing accuracy of measurements to the tenth shares of percent.